If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 = 8x + -75 Reorder the terms: 21 = -75 + 8x Solving 21 = -75 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 21 + -8x = -75 + 8x + -8x Combine like terms: 8x + -8x = 0 21 + -8x = -75 + 0 21 + -8x = -75 Add '-21' to each side of the equation. 21 + -21 + -8x = -75 + -21 Combine like terms: 21 + -21 = 0 0 + -8x = -75 + -21 -8x = -75 + -21 Combine like terms: -75 + -21 = -96 -8x = -96 Divide each side by '-8'. x = 12 Simplifying x = 12
| 6a+5x=36 | | (4s+4)(4s-4)=0 | | 3x+y+z=14 | | (3r-1)(4r-3)=0 | | 15-8m=73 | | -8x+6x-7x=3x(4-3)-5x-15 | | 98p=197 | | 5/3= | | 170-2x=25x+20 | | -5=15+4x | | 5x-x+3=-x+7 | | 5-9x=37-16x | | 3n+4=56 | | 3(4i)+2(7i)= | | 3(2x-3)-2x=8-2(3x+1) | | 5x-8-3x-9=-12x+11 | | y^2+4x-4y-12=0 | | 10n+5=9n | | 23+1z=3 | | 3(t+2)=9(t-2) | | e+2(e+4)+3e=56 | | 99-2x=4-9x | | x^2-9xy-10y^2=0 | | 87-6x=10+23x | | 6x-2(x+5)=4x-1 | | b+(b+80)+.07(b+b+80)=294.25 | | 0=70n-n^2 | | x=(7x)(9x-7) | | y-45=54 | | -(7y+1)-(-6y-8)=2 | | 4g+3h=5i | | 5-3.6X=1.3X+8 |